Threats, Drivers, and Conservation Imperative of Agrobiodiversity - Chaudhary, P.; Bhatta, S.; Aryal, K.; Joshi, B.K.; Gauchan, D. (Journal of Agriculture and Environment, 2020)
Agrobiodiversity underpins food, nutrition and livelihood security, ecosystem and environmental health, and climate change resilience but it is under threat of extinction. This paper highlights threats of agrobiodiversity, its drivers and conservation imperatives. Review shows prior to the green revolution, several crops and varieties were found in situ and on-farm but the number has declined since then. Extinction is contributing to decline in crop productivity and resilience and consequently the long-term sustainability of human wellbeing. Extinction is attributable to various natural and man-made factors. Various international and national level efforts are underway but not adequate to curb the loss. Therefore, further efforts are required to conserve and utilize agrobiodiversity, which will require concerted efforts in exploring agrobiodiversity, identifying drivers of loss and bolstering conservation efforts. This can be done through implementation of biodiversity-friendly legislations, actions and incentive mechanisms adhering to relevant global and national level policies, negotiations and conventions.